2011
DOI: 10.1111/j.1365-2141.2011.08969.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on the investigation and management of follicular lymphoma

Abstract: The guideline group was selected to be representative of UK-based medical experts and patient's representatives. MEDLINE and EMBASE were searched systematically for publications in English from 1980-2010 using the key words follicular lymphoma, non-Hodgkin lymphoma and low-grade lymphoma. The writing group produced the draft guideline, which was subsequently revised by consensus by members of the Haemato-oncology Task Force of the British Committee for Standards in Haematology (BCSH). The guideline was then re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 132 publications
(199 reference statements)
1
34
0
3
Order By: Relevance
“…[27][28][29]32,33 Given that the use of larger field sizes has not been found to improve OS and there are concerns about radiation-induced toxicity and secondary malignancy, IFRT has been considered the standard field size in clinical practice. [16][17][18][19][20] Despite being considered the standard of care, RT for localized FL is greatly underused in the United States. A large Surveillance, Epidemiology, and End Results (SEER) database analysis of 6568 patients with low-grade localized FL in the United States found that RT was associated with significantly improved OS compared with non-RT approaches (P < .0001); however, only a third of the patients received upfront RT over the 30-year study period.…”
Section: Radiotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29]32,33 Given that the use of larger field sizes has not been found to improve OS and there are concerns about radiation-induced toxicity and secondary malignancy, IFRT has been considered the standard field size in clinical practice. [16][17][18][19][20] Despite being considered the standard of care, RT for localized FL is greatly underused in the United States. A large Surveillance, Epidemiology, and End Results (SEER) database analysis of 6568 patients with low-grade localized FL in the United States found that RT was associated with significantly improved OS compared with non-RT approaches (P < .0001); however, only a third of the patients received upfront RT over the 30-year study period.…”
Section: Radiotherapymentioning
confidence: 99%
“…4,13,14 Several international guidelines exist for FL, including the National Comprehensive Cancer Network (NCCN), the European Society for Medical Oncology (ESMO), the British Committee for Standards in Haematology, the Italian Society of Hematology/Italian Society of Experimental Hematology/Italian Group for Bone Marrow Transplantation, as well as Spanish guidelines. [16][17][18][19][20] However, in Canada, there is no unified national guideline for FL. Although provincial guidelines exist, they differ across provinces and are primarily based on the availability of agents in the provincial formulary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on trials showing no benefit of immediate chemotherapy in patients with a low tumor burden, 73,74 current guidelines recommend a WW approach, deferring treatment initiation until worsening of disease and/or clinical symptoms appear. 75 Most patients with a low tumor burden under WW have an improved quality of life for an average period of 2.5 years by delaying exposure to the toxic side-effects of chemotherapy, the reduced number of hospital visits and related interventions (therapeutic agents administration, blood puncture, etc.). Yet 60-80% will eventually progress towards high tumor burden within a relatively short time, and will require radio/chemotherapy in a setting in which treatment may be not curative at that stage of disease.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…For patients with localized disease, radiotherapy has been proposed to provide long-term benefit (50% freedom from treatment failure at 10 years). [75][76][77] The role of rituximab-based therapy in the management of early stage FL is also under investigation. Although based on small numbers, it is notable that in a series of PFL treated with rituximab or radiotherapy none of the patients progressed to overt FL after seven years of follow up, compared to 53% when left untreated.…”
Section: Clinical Perspectivesmentioning
confidence: 99%